Stand-Alone Middle Meningeal Artery Embolization for Treatment of Giant Chronic Subdural Hematoma in Elderly Frail Patients: A Case Series. (18th December 2021) - Cannarsa, Gregory J; Olexa, Joshua; Chryssikos, Timothy; Wessell, Aaron P; Sharma, Ashish; Miller, Timothy R; Jindal, Gaurav; Aarabi, Bizhan; Gandhi, Dheeraj
Graphical Abstract: